Penerapan Teknologi Absensi Online Sebagai Implikasi E-Government dalam Optimalisasi Manajemen Kehadiran Guru - Dwi Nurfarisa; Tri Cahyo Nugroho (Prosiding SISFOTEK, 2023)
This research discusses the application of online attendance technology as part of the implementation of e-government in optimizing teacher attendance management. The aim of this research is to analyze the implementation of online attendance which is reviewed in three aspects including support, capacity and value. The method used is descriptive qualitative with cross-checking data analysis which includes interviews, observation and document review. The research results show that in the support aspect, the use of the online attendance application is supported by a regional secretariat circular which requires ASNs to use the attendance application, including teachers. In the capacity aspect, the teachers are able to use the application proficiently, this is because previous socialization has been carried out. In the value aspect, it can be said that implementing online attendance not only makes the process of recording attendance easier but also increases discipline. Implementing online attendance can support attendance management and improve discipline